Alternative short tests for inspection and maintenance of in-use cars with respect to their emissions performance - Samaras, Zissis; Joumard, Robert; Vernet, Isabelle; Hassel, Dieter; Weber, Franz Josef; Rijkeboer, Rudolf; Zachariadis, Theodoros (My University, 1998)
This paper presents the first results of a project aimed at evaluation of a number of short tests that can be alternatively used for Inspection and Maintenance of in-use cars emissions performance. For this purpose, a large number of in-use cars from four European countries was tested according to a test protocol that included a wide selection of short tests (idle and fast idle tests, a steady-state loaded test and short transient loaded tests), in addition to the legislated New European Driving Cycle and a number of real-world cycles. The test results were statistically analysed in a number of different combinations, with the objective to define a set of reasonable cutpoints, taking into account various criteria such as errors of commission, errors of omission, excess emitter identification rate and excess emission identification rate.
Keywords: Exhaust emissions; Inspection; Legislation; Maintenance; Short cycles